Impact of the economic crisis on children's health in Catalonia: a before–after approach. Issue 8 (23rd August 2013) - Rajmil, Luis; Medina-Bustos, Antonia; Fernández de Sanmamed, María-José; Mompart-Penina, Anna
Abstract : Objectives: To analyse changes in the family living conditions of children in Catalonia between 2006 and the 2010–2012 period, and to study associations between these changes and health outcomes. Design: A before–after analysis of two cross-sectional surveys. Setting: Population younger than 15 years of age from Catalonia, Spain. Participants: Representative samples of children in the 2006 Catalan Health Survey (ESCA), baseline, before the crisis; n=2200) and the first four waves of ESCA 2010–2012 (after start of the crisis, n=1967). Main outcome measures: Overweight/obesity, health behaviour, mental health and health-related quality of life (HRQOL). Logistic regression and multiple linear regression models were used to analyse the influence of changes in family conditions on outcome measures, including interaction terms to describe the potential influence of the study period on the results. Results: The percentage of unemployed families rose from 9.1% (2006) to 20.6% (2010–2012), with inequalities by level of education. Overweight/obesity increased from 18.4% (95% CI 16.5% to 20.4%) to 26.9% (24.6% to 29.2%) in 2010–2012, and inequalities related to maternal education and employment status persisted. Eating habits have improved in 2010–2012 in disadvantaged families (ie, junk food consumption improved in families with a maternal primary education level; beta (B)=2.85; 0.83 to 4.88, for the survey interaction by primary education level). An improvement in HRQOL was found in the second survey (B=6.07; 4.15 to 7.99), although children whose mothers had a primary education showed poorer HRQOL scores in this survey than in 2006 (B=−4.14; −7.17 to −1.12). Conclusions: Although some health-related behaviour improved during the study period, childhood obesity increased and inequalities in HRQOL appeared. Policy measures that fight against these inequalities should be urgently implemented to avoid their negative impact on the health of future generations of Catalans.